Five-Factor Response Surface Optimisation of Hydrochloric Acid Dissolution of Alumina from a Nigerian Clay - Orugba, H. O.; Onukwuli, O. D.; Babayemi, A. K.; Umezuegbu, J. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The major challenge encountered in the process of making the acid dissolution of alumina from clays economically viable is the determination of the optimum conditions of the key process variables in order to enhance efficient recovery. High alumina recovery from clays can be achieved by determining the optimum conditions of the process variables during optimization. In this research, using the experimental design, the combined effects of five independent variables (calcination temperature, leaching temperature, acid concentration, stirring speed and liquid/solid ratio) on the yield of alumina from the local clay was studied and the second order polynomial regression equation was developed to evaluate the influence of the five independent variables on alumina yield. Model adequacy test was performed using the analysis of variance (ANOVA) and 0.9209 was obtained as the correlation value between the experimental responses and the predicted responses.  The optimum yield of alumina was obtained as 80.07% at 677.27°C heat of activation; 65.18°C leaching temperature; 1.9mol/cm3HCl concentration; 10.36 liquid-solid weight ratio and 442.92rpm stirring speed.